Pemulihan Pendapatan UMKM di Era Pandemi Melalui Digital Marketing - Shavareydam Abdillah Harahap; Diva Cahyatini; Friska Nadila; Kamilah Kamilah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article discusses the recovery of MSME income in Sumber Mulyorejo Village, East Binjai District in the pandemic era through digital marketing. In this service activity, digital marketing and online business training were carried out as a form of digital-based villager empowerment. This article is a study of the results of the implementation of service, the study is in the form of descriptive with a library research approach sourced from books and journals. This service activity uses a participatory rural approach in the form of direct counseling to the community. Extension activities aim to provide an understanding of the use of social media as a marketing tool in the digital era. The participants involved in the training were residents of Sumber Mulyorejo Village. As a result, residents became interested in knowing and trying to use social media, especially the concept of digital marketing for product marketing, so it was hoped that it could be applied to promote local products or village potentials by applying the knowledge provided by the KKN 146 UINSU group.